Analysis of Risk Assessment in Highway Projects Using Importance Index. Issue 1 (April 2021) - Garg, Rahul; Rawat, Saurabh
Abstract: Road construction delay is considered to be repetitive problems in the construction industry causing various negative effects on project success in terms of time, money, and quality. Therefore it is essential to identify and analyze the causes of highway construction delay. The main purpose of this study is to identify the causes of delay affecting highway construction projects. 40 delay causes were identified using a literature review and were categorized into 13 groups. Data were collected through a questionnaire survey. Questionnaires were distributed to 425 respondents out of which 388 were received. Values of Frequency and severity of occurrence of delay causes are calculated for getting values of importance index. Risk factors are ranked using the importance index. Results indicate that the top five harmful delay factors are change in design, Delayed payment, Inaccurate details in drawings, Financial difficulties, and Poor project management, and least five harmful delay factors are Physical obstruction during construction, Road blockage, and traffic at the construction site, Labor dispute, Sudden change in government law and skilled labor. The findings can help the Project team to decrease highway construction delays.